The Development of PBL-based Water Cycle Diorama Media to Improve Grade V Learning Outcomes - Dewi, Rantika Puspita; Tyas, Dewi Nilam (Jurnal Prima Edukasia, 2025)
The lack of use of learning media at Kutowinangun 08 Salatiga Elementary School causes the learning outcomes of water cycle material in class V to be low. Based on these problems, this study aims to develop and test the feasibility and effectiveness of diorama media on water cycle material, hereinafter referred to as PBL-based SIAR in Grade V. This R&D research adapted nine of the ten steps of the Borg and Gall development model. Quantitative and qualitative data were collected using both test and non-test techniques, including questionnaire instruments, observation, interviews, and documentation. These data were then analyzed both descriptively and inferentially. The developed media was validated by media experts and material experts, who applied very valid criteria, achieving percentages of 82% and 90.67%. Based on the results of the paired sample t-test, it is evident that the significance value is 0.000 < 0.05, indicating that H0 is rejected and Ha is accepted. This means that the product developed is effective in improving student learning outcomes. The N-Gain test results obtained a gain value of 0.64 (medium). Based on the results of the response questionnaire, it was received very positively by teachers and students. From these results, it can be concluded that the diorama media SIAR (water cycle) based on PBL developed is highly feasible and effective in improving the learning outcomes of IPAS fifth-grade students at Kutowinangun 08 Salatiga State Elementary School. The contribution of this research to existing knowledge is twofold: it serves as an alternative and enriches the literature on SIAR diorama media based on PBL, which has been proven effective in improving learning outcomes for water cycle material, and provides new insights as a reference for further learning.